Blastomycosis Masquerading as Severe Community-Acquired Pneumonia in a Nonendemic Region: A Case Report and Literature Review. Issue 3 (May 2018) - Foster, Gabriel P.; Fessler, David; Kociol, Robb; Witkin, Alison; Hale, Andrew
Abstract : Abstract: A case is presented of an otherwise healthy, middle-aged man who presented in Boston, Mass, with fever and cough and was initially diagnosed as having community-acquired pneumonia. Despite an outpatient course of azithromycin and then levofloxacin, he clinically worsened over 2 weeks, eventually developing acute respiratory distress syndrome. Alternative causes were then considered, with workup revealing severe pulmonary blastomycosis infection. Despite eventual appropriate antifungal therapy, he had advanced disease at the time of his delayed diagnosis and died because of complications of the infection. The patient's presenting chest radiograph, potassium hydroxide preparation of bronchoscopy specimen, and silver stain of lung tissue with massive fungal disease burden are presented as clinical images. Abstract : A fatal case is presented of pulmonary blastomycosis in an immunocompetent, healthy man with minimal exposure to an endemic region. This case highlights the potential severity of blastomycosis infection, and that index of suspicion for this pathogen should remain high when typical antibiotic therapy is failing.